Revision of the dwarf cannibal snails (Nata s.l.) of southern Africa—Nata s.s. and Natella (Mollusca: Gastropoda: Rhytididae), with description of three new species - Herbert, David G.; Moussalli, Adnan (Zootaxa, 2016)
This paper represents the second part of our revisionary studies on the rhytidid fauna of southern Africa. The species discussed belong to the taxon Nata s.l. in which we recognise two genus-level lineages, Nata s.s. and Natella with six (three new) and one species respectively. We update the species-level taxonomy extensively in the light of new molecular and morphological data, and provide a comprehensive revision of all species, including keys. Detailed comparative morphological observations are provided for the distal reproductive tract, pulmonary cavity, mantle edge, radula and suprapedal gland. In addition, we present a summary of biological and ecological data including information on habitat preferences, feeding, prey items and mating behaviour. Although the two genera are well circumscribed in terms of both internal anatomy and molecular data, shell morphology is highly conserved, and species discrimination using shell characters alone is difficult. We have discovered three undescribed species within Nata and there is evidence that further research of a phylogeographic nature may uncover additional cryptic diversity. The geographic distributions of the species are discussed in relation to regional vegetation patterns and, as with the larger cannibal snail radiation, the Albany Thicket Biome emerges as a focus of endemism. Observations on the conservation status of all species are provided. New species: Nata aequiplicata sp. nov., Nata erugata sp. nov. and Nata watsoni sp. nov. Revised status: Natalina caffrula Melvill & Ponsonby, 1898 is transferred to the genus Nata and thought to be a synonym of Nata dumeticola (Benson, 1851).